Penerapan Pelatihan LEARN Model Untuk Meningkatkan Penanganan Keluhan Tamu di Evolution Restaurant and Bar Four Points by Sheraton Bali Ungasan - Pratama, Ida Bagus Gede Yogi Wisma; Trianasari; Andiani, Nyoman Dini (Universitas Pendidikan Ganesha, 2025)
This research aims to identify the use of the LEARN MODEL method used to handle complaints by waiters/waitresses at the Evolution Restaurant and Bart Four Points by Sheraton Bali Ungasan, using a qualitative descriptive method. The study used qualitative methods, where data were collected through observations, interviews and documentation, and documentation. The results of this research show that handling customer complaints by applying empathy to angry customers makes feelings of empathy very important when dealing with angry consumers. Speed in Complaint Handling problems quickly can turn dissatisfaction into satisfaction and increase consumer loyalty. Complaint analysis and evaluation collecting and analyzing information from consumer complaints can provide a valuable understanding of aspects that need to be improved. Improving the quality of service for employees who have adequate knowledge and skills in handling complaints can provide a better experience for consumers. Good Communication Clear and easy to understand communication is crucial in conveying information and solutions to customers. This research makes a practical and theoretical contribution to how to respond to good complaints from customers who come to stay at hotels